Psychological Well-Being of Divorce Permitting Team in BKPSDM Sragen - Willy Anggita Rimba Pramesti; Sri Ernawati (CV Projurnal Mitra Publikasi, 2025)
This study aims to look at the dynamics of psychological well-being in employees of the divorce licensing section at BKPSDM Sragen. This research identifies factors that influence the psychological well-being of employees in dealing with sensitive tasks. The research method used is a descriptive qualitative approach. Data were collected through in-depth interview techniques, observation, and documentation. The informants involved were four employees. The results show that psychological well-being is influenced by individual factors such as self-acceptance and personal growth, as well as external factors such as positive relationships and life goals. This research recommends developing better organisational support to improve employees' psychological well-being.